EFFECTIVENESS OF BOTULISM TOXIN IN THE TREATMENT OF ANAL FISSURE - Bashir, Umar; Raza, Ahmed; Zafar, Afsheen; Majeed, Farhan Ahmed; Shabbir, Hassan; Mumtaz, Moazzam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the effectiveness, feasibility and acceptability of botulinum toxin in healing chronic anal fissures in our population. Study Design: Prospective observational study. Place and Duration of Study: Combined Military Hospital, Multan, from Jan 2019 till Dec 2019. Methodology: Eighty patients were enrolled in the study out of which 72 completed the study. 33 IU of botulinum toxin A was injected in the intersphincteric groove in the perianal region. Outcome measures for effectiveness included pain score and fissure healing rates at 2, 6, 16 and 24 weeks after the injection. Healing rate was calculated as percentage and pre and post injection pain scores were compared by using paired sample t-test. Patient acceptability was assessed based on the proportion of patients who accepted the treatment. The average treatment cost was also calculated. Results: A total number of 250 patients were found to be eligible for the study. A purposive sampling technique was used. Eighty patients took part in the study with an acceptability rate of 32%. Seventy two patients completed the study with a completion rate of 90%. Amongst 72 patients, 47 (65.3%) were female and 25 (34.7%) were male. The complete healing rate after 3 months of botulinum toxin injection was 49 (68.1%). There was a significant reduction in pain scores at 2, 6, 16, and 24 weeks of study (p<0.01). Conclusion: The study supports that Botulinum toxin is an acceptable and effective treatment for anal fissure. Keywords: , , .